Comparative Analysis of Transportation Education Systems - Damoyanto Purba (Lembaga Einstein College (LEC), 2024)
This research conducts a comparative analysis of transportation education systems, focusing on curriculum design, teaching methods, industry partnerships, student outcomes, and program quality. Qualitative research methods, including interviews with 39 cadets, are used to gather data. The findings highlight the importance of aligning education with industry needs, innovative teaching methods, strong industry partnerships, and prioritizing student outcomes. The research indicates that while the transportation education program is effective, there is room for improvement, such as updating the curriculum, expanding collaboration with industry partners, and promoting continuous improvement. Overall, this research contributes to enhancing the quality and relevance of transportation education programs, preparing students for successful careers in the global transportation industry